An unusual case of multifocal central serous chorioretinopathy with low serum cortisol managed using eplerenone - Kanika Aggarwal (Indian Journal of Ophthalmology, 2019)
In this report, we describe a rare case of a 44-year-old Asian male with acute central serous chorioretinopathy (CSC) with bullous exudative retinal detachment. Endocrinology evaluation revealed hypothalamic–pituitary–adrenal axis suppression with low serum cortisol. Furthermore, neuroimaging revealed the presence of a pituitary microadenoma. He was treated with systemic eplerenone and hydrocortisone. After 12 weeks, bullous detachment completely resolved. Our case is a unique description of acute CSC with underlying low serum cortisol levels that responded to treatment with mineralocorticoid antagonist. This case highlights the various endocrine abnormalities other than the raised serum cortisol that can occur in patients with CSC.